KUALITAS SOAL BUATAN GURU DAN DINAS PENDIDIKAN BIDANG STUDI KIMIA - Nugraheni, Yuliana Putri; Widodo, A. Tri; Sugiyo, Warlan (Universitas Negeri Semarang, 2013)
Curriculum enactment of SBC lead to variations in the manufacturing of test questions. Problem in some districts created by the teacher, while some other districts compiled by the Department of Education (MGMP). In its function as a tool to determine student achievement of competence, the test must be regarded as a good problem to meet the criteria of validity, reliability, level of difficulty, different power, objectivity, praktikabilitas, and economics. This study aims to determine the quality of the final semester of odd-test questions and the teacher made ​​the education field of study of chemistry. The method used in this study is the method of documentation. Samples were analyzed to determine the students' responses about the quality of the content of student work. The results showed that the question of teacher-made and not yet fully meet the education criteria about the quality parameters. Both of these types of problems can not be said as a test of good to be used as a general test questions semester. Based on these results concluded that the question of artificial Odd Semester End of Deuteronomy in the District of Semarang and Teacher Education Office Pemalang district to subject areas of chemistry in 2011/2012 do not meet the criteria of a good question.